The γ-parameter of anomalous diffusion quantified in human brain by MRI depends on local magnetic susceptibility differences - Caporale, A.; Palombo, M.; Macaluso, E.; Guerreri, M.; Bozzali, M.; Capuani, S. (NeuroImage (Orlando, Fla.), 2017)
Motivated by previous results obtained in vitro, we investigated the dependence of the anomalous diffusion (AD) MRI technique on local magnetic susceptibility differences (Δχ) driven by magnetic field inhomogeneity in human brains. The AD-imaging contrast investigated here is quantified by the stretched-exponential parameter γ, extracted from diffusion weighted (DW) data collected by varying diffusion gradient strengths. We performed T2* and DW experiments in eight healthy subjects at 3.0T. T2*-weighted images at different TEs=(10,20,35,55)ms and DW-EPI images with fourteen b-values from 0 to 5000s/mm2 were acquired. AD-metrics and Diffusion Tensor Imaging (DTI) parameters were compared and correlated to R2* and to Δχ values taken from literature for the gray (GM) and the white (WM) matter. Pearson's correlation test and Analysis of Variance with Bonferroni post-hoc test were used. Significant strong linear correlations were found between AD γ-metrics and R2* in both GM and WM of the human brain, but not between DTI-metrics and R2*. Depending on Δχ driven magnetic field inhomogeneity, the new contrast provided by AD-γ imaging reflects Δχ due to differences in myelin orientation and iron content within selected regions in the WM and GM, respectively. This feature of the AD-γ imaging due to the fact that γ is quantified by using MRI, may be an alternative strategy to investigate, at high magnetic fields, microstructural changes in myelin, and alterations due to iron accumulation. Possible clinical applications might be in the field of neurodegenerative diseases. [Display omitted]